2009
DOI: 10.1159/000222673
|View full text |Cite
|
Sign up to set email alerts
|

BCG Priming of Dendritic Cells Enhances T Regulatory and Th1 Function and Suppresses Allergen-Induced Th2 Function in vitro and in vivo

Abstract: Background: The inverse correlation of mycobacterial infection with asthma prevalence and the inhibitory effects of vaccination with Bacille Calmette-Guérin (BCG) on airway hyperreactivity in asthma models suggest modulation of dendritic cell (DC) and T cell functions by mycobacterial compounds. Methods: To delineate these immunological effects, the immunogenicity of BCG Copenhagen, BCG Chicago and BCG Pasteur was compared in a mouse model. Bone marrow-derived dendritic cells (BMDCs) from BALB/c mice were stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 62 publications
5
23
0
Order By: Relevance
“…We show that BCG-infected DCs actively participate in neutrophil recruitment. Consistent with our observations, Ahrens and colleagues (45) have also shown that BCG-infected DCs administered to mouse airways induced strong neutrophil recruitment. Therefore, DCs chronically infected with mycobacteria present in the mature granuloma (9) actively participate in the prolonged recruitment of neutrophils.…”
Section: Discussionsupporting
confidence: 93%
“…We show that BCG-infected DCs actively participate in neutrophil recruitment. Consistent with our observations, Ahrens and colleagues (45) have also shown that BCG-infected DCs administered to mouse airways induced strong neutrophil recruitment. Therefore, DCs chronically infected with mycobacteria present in the mature granuloma (9) actively participate in the prolonged recruitment of neutrophils.…”
Section: Discussionsupporting
confidence: 93%
“…(21) A study investigating a cohort of low-income children in Salvador, Brazil, reported that the prevalence of asthma attributable to atopy was only 20% and that asthma is most strongly correlated with poor housing conditions and sanitation (unpublished data). One group of authors (15) investigated the effect of BCG vaccination on an experimental model of asthma in mice and confirmed the previous reports of suppression of the Th2 inflammatory response in the airways, accompanied by the activation of regulatory T cells. However, concomitant neutrophilic inflammation related to the stimulation of Th1 cells was also observed.…”
supporting
confidence: 71%
“…Based on this premise, various studies have been conducted in an attempt to identify interventions that might be incorporated into strategies to attenuate or prevent inflammation in asthma. (3,15) In practice, however, this theory is not tenable. Because of the plurality of the immune response, the various inflammatory phenotypes of asthma, the genetic diversity, the environmental diversity and the various opinions regarding the timing of the intervention, this is a complex issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that DCs played an important role in BCG infection-mediated inhibition of allergy to ragweed [8]. In addition, intranasal administration of BCG modulated ovalbumin (OVA)-pulsed bone marrow-derived stem cells, increased the number of Foxp3+ cells in bronchial lymph nodes and reduced OVA-induced eosinophilic airway inflammation [9]. Hence, we hypothesized that DCs might also play a central role in Der p 2 rBCG-mediated inhibition of allergic airway inflammation.…”
Section: Introductionmentioning
confidence: 99%